Benefits of E-Learning to Learning Media Using Whatsapp in the Learning Process in Higher Educations in the Middle of the Spread of Covid -19 - Rizka Widayanti; Dwi Sari Ida Aflaha; Basariah Basariah; Aswin Saputra (Budapest International Research and Critics University, 2022)
In the modern era at this time information technology has experienced very rapid development, especially in the world of education, the use and use of the internet in education continues to grow. E-learning is a form of learning that utilizes electronic devices, whether using internet access or not. In the world of education, the use of internet access has been widely used for the use of applications/systems as learning media. Thus, the purpose of this study is as follows to determine the benefits of e-learning learning media using WhatsApp in the learning process in universities amid the spread of COVID-19. The method used in this research is qualitative research, which is a type of research that produces findings that cannot be achieved using statistical procedures or other quantitative methods. The subject of this research is the second semester students of the curriculum subject of the Indonesian language education study program as many as 39 resource persons using observation and interview data collection techniques. The results of this study are e-learning learning media using whatsapp is very useful to improve the learning process for students, especially during the pandemic, Not only that, the use of WhatsApp is also to complete the means of sending assignments from lecturers to students because from the aspect of time it is very efficient, it doesn't take too long for lecture assignments to be sent easily and immediately received by the lecturer concerned. Future suggestions are expected as users to be smarter in placing WhatsApp usage so they don't use and take advantage of technological sophistication for things that are less useful.